The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/ijms19123791
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to Palmitate Impairs Insulin Signaling in an Intestinal L-cell Line: A Possible Shift from GLP-1 to Glucagon Production

Abstract: Obesity and type 2 diabetes mellitus (T2DM) are characterized by insulin resistance and impaired glucagon-like peptide-1 (GLP-1) secretion/function. Lipotoxicity, a chronic elevation of free fatty acids in the blood, could affect insulin-signaling in many peripheral tissues. To date, the effects of lipotoxicity on the insulin receptor and insulin resistance in the intestinal L-cells need to be elucidated. Moreover, recent observations indicate that L-cells may be able to process not only GLP-1 but also glucago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 92 publications
(126 reference statements)
2
28
0
Order By: Relevance
“…Previous studies have shown a stimulatory effect of fatty acids on glucagon secretion from rodent islets and cell lines and mechanisms involved are signaling through fatty acid G‐protein coupled receptors beta‐oxidation of fatty acids and activation of L‐type Ca 2+ channels . Interestingly, fatty acid palmitate was recently shown to induce a switch to a glucagon secreting phenotype in an intestinal GLP‐1 secreting cell, raising the possibility of fatty acids to induce extrapancreatic glucagon . In the in vivo data, there was a positive relationship between fasting insulin and fasting glucagon concentrations and this was found in the obesity group as well as in the lean group of children and adolescents.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have shown a stimulatory effect of fatty acids on glucagon secretion from rodent islets and cell lines and mechanisms involved are signaling through fatty acid G‐protein coupled receptors beta‐oxidation of fatty acids and activation of L‐type Ca 2+ channels . Interestingly, fatty acid palmitate was recently shown to induce a switch to a glucagon secreting phenotype in an intestinal GLP‐1 secreting cell, raising the possibility of fatty acids to induce extrapancreatic glucagon . In the in vivo data, there was a positive relationship between fasting insulin and fasting glucagon concentrations and this was found in the obesity group as well as in the lean group of children and adolescents.…”
Section: Discussionmentioning
confidence: 82%
“…Consistent with our model, Martchenko and colleagues [46] have recently reported fatty acid-induced lowering of circadian release of GLP-1 from L-cells as a result of decreased Bmal1 expression. Similarly, Filipello et al [47] reported decreased insulin-dependent GLP-1 secretion from L-cell-derived GLUTag cells, and increased glucagon release, upon fatty acid treatment. Similar findings on GLP-1 secretion were reported by others [48,49], whist long chain saturated (palmitate) but not unsaturated (oleate) fatty acids lead to L-cell apoptosis [50].…”
Section: Discussionmentioning
confidence: 88%
“…Human hepatoblastoma cell line HepG2 was cultured as previously reported . To obtain in vitro models of NAFL or NASH, HepG2 at 75% confluence were exposed to a mixture of oleate/palmitate or only palmitate at a final fatty acid concentration of 0.5 mM for 48 h respectively …”
Section: In Vitro Cell Culture Experimentsmentioning
confidence: 99%